A cell-based evaluation of human tyrosinase-mediated metabolic activation of leukoderma-inducing phenolic compounds. Issue 2 (November 2022) - Nishimaki-Mogami, Tomoko; Ito, Shosuke; Cui, Hongyan; Akiyama, Takumi; Tamehiro, Norimasa; Adachi, Reiko; Wakamatsu, Kazumasa; Ikarashi, Yoshiaki; Kondo, Kazunari
Abstract: Background: Chemical leukoderma is a skin depigmentation disorder induced through contact with certain chemicals, most of which have a p -substituted phenol structure similar to the melanin precursor tyrosine. The tyrosinase-catalyzed oxidation of phenols to highly reactive o -quinone metabolites is a critical step in inducing leukoderma through the production of melanocyte-specific damage and immunological responses. Objective: Our aim was to find an effective method to evaluate the formation of o -quinone by human tyrosinase and subsequent cellular reactions. Methods: Human tyrosinase-expressing 293T cells were exposed to various phenolic compounds, after which the reactive o -quinones generated were identified as adducts of cellular thiols. We further examined whether the o -quinone formation induces reductions in cellular GSH or viability. Results: Among the chemicals tested, all 7 leukoderma-inducing phenols/catechol (rhododendrol, raspberry ketone, monobenzone, 4- tert -butylphenol, 4- tert -butylcatechol, 4- S -cysteaminylphenol and p -cresol) were oxidized to o -quinone metabolites and were detected as adducts of cellular glutathione and cysteine, leading to cellular glutathione reduction, whereas 2- S -cysteaminylphenol and 4- n -butylresorcinol were not. In vitro analysis using a soluble variant of human tyrosinase revealed a similar substrate-specificity. Some leukoderma-inducing phenols exhibited tyrosinase-dependent cytotoxicity in this cell model and in B16BL6 melanoma cells where tyrosinase expression was effectively modulated by siRNA knockdown. Conclusion: We developed a cell-based metabolite analytical method to detect human tyrosinase-catalyzed formation of o -quinone from phenolic compounds by analyzing their thiol-adducts. The detailed analysis of each metabolite was superior in sensitivity and specificity compared to cytotoxicity assays for detecting known leukoderma-inducing phenols, providing an effective strategy for safety evaluation of chemicals. Highlights: The tyrosinase-mediated formation of o -quinone from phenols can trigger leukoderma. Ectopic expression of human tyrosinase converts rhododendrol to quinone metabolites. Rhododendrol-quinones generated bind to glutathione and cysteine in this cell model. A series of leukoderma-inducing phenols is converted to quinone-thiol adducts. Thiol-adduct analysis is more sensitive and specific than cytotoxicity assays.